The exploitation of biomass for building space heating in Greece: Energy, environmental and economic considerations - Michopoulos, Apostolos; Skoulou, V.; Voulgari, V.; Tsikaloudaki, A.; Kyriakis, N. A. (My University, 2014)
The exploitation of forest and agricultural biomass residues for energy production may offer significant advantages to the energy policy of the relevant country, but it strongly depends on a number of financial, technological and political factors. The work in hand focuses on the investigation of the energy, environmental and financial benefits, resulting from the exploitation of forest and agricultural biomass residues, fully substituting the conventional fuel (diesel oil) for building space heating in Greece. For this investigation, the energy needs of a representative building are determined using the EnergyPlus software, assuming that the building is located across the various climate zones of Greece. Based on the resulting thermal energy needs, the primary energy consumption and the corresponding emissions are determined, while an elementary fiscal analysis is also performed. The results show that significant financial benefits for the end-user are associated with the substitution examined, even though increased emissions and primary energy consumption have been derived.
Keywords: Residual biomass; Combustion; Emissions; Energy consumption; Residential buildings